RiTAS Application Oriented to Ausubel Learning Theory for Social Studies Content: Validity and Feasibility - Ferdiansyah, Ade Citia Dewi; Wulandari, I Gusti Agung Ayu (Universitas Pendidikan Ganesha, 2021)
The implementation of online learning tends to make students bored if they only use learning media in the form of videos taken from YouTube and assignments given by the teacher through Google Classroom and Whatsapp groups. The limited ability of teachers to use digital learning media is the cause of the monotony of learning media during online learning. The purpose of this study is to describe the design and validity of the learning media application being developed. This development research applies the ADDIE model. Data collection was carried out by using a questionnaire method with a questionnaire instrument. The data analysis used qualitative and quantitative descriptive analysis methods. The subject of this development research is learning media in the form of an android application. Furthermore, the subject matter is reviewed by expert validators, learning design experts, media experts. Finally, the students conducted trials individually and in small groups. The results of data analysis based on media validation by material experts obtained a score of 92.8% with very good qualifications, learning design experts got a score of 87.5% with good qualifications, learning media experts got a score of 85% with good qualifications. The results of individual trials on 3 students obtained a score of 90.1% with very good qualifications and tests through small group testing on 9 students obtained a score of 90.9% with very good qualifications. Based on the results of the analysis of product test data by experts and the results of testing on students, it is concluded that this research learning media is valid and suitable for use in learning by grade VI students.